THE INFLUENCE OF E-SERVICE QUALITY, E-SATISFACTION, AND E-WORD OF MOUTH TOWARD REVISIT INTENTION ON TOKOPEDIA WEBSITE IN PADANG CITY - Jerri Andrian; Okki Trinanda (Jurnal Ecogen, 2019)
Purpose - This research aims to analyze: (1) The Influence of E-Service Quality toward E-Satisfaction on Tokopedia Website in Padang city (2) The Influence of E-Service Quality toward E-Word of Mouth on Tokopedia Website in Padang city (3) The Influence of E-Satisfaction toward E-Word of Mouth on Tokopedia Website in Padang city (4) The Influence of E-Word of Mouth toward Revisit Intention on Tokopedia Website in Padang city. Methodology - The type of this research is Causative research. The population on this research is all the consumer of Tokopedia in Padang who revisit Tokopedia website with the total sample is 150 person which was taken by using purposive sampling due to unknown the number of population. Finding - Regarding the causal model proposed, the data confirm the relationship set out in the hypothesis. It can therefore be stated that (1) E-Service Quality has a positive effect and significant to E-Satisfaction (2) E- Service Quality has a positive effect and significant to E-Word of Mouth (3) E-Satisfaction has a positive effect and significant to E-Word of Mouth (4) E-Word of Mouth has a positive effect and significant to Revisit Intention. Conclusion - The analysis highlights the positive influence which taking part in the E-Service Quality, E- Satisfaction and E-Word of Mouth toward Revisit Intention. This is the clearly shows in this relationship from the empirical point-of-view. Limitation - This research only limit with the some variableKeyword: E-Service Quality, E-Satisfaction, E-Word of Mouth, Revisit Intention